বাজেট, পরিকল্পনা দারিদ্র বিমোচন - মাহমুদ, আনু (ঢাকা : হাক্কানী পাবলিশার্স : Paribeśaka Papulāra Pābaliśārsa, 1998)
On the budget of Bangladesh and its role in eradication of poverty.
In Bengali.
Keywords: Budget -- Bangladesh; Poverty -- Bangladesh; Bangladesh -- Economic policy